The Role of Intestinal Microbial Metabolites in the Immunity of Equine Animals Infected With Horse Botflies - Hu, Dini; Tang, Yujun; Wang, Chen; Qi, Yingjie; Ente, Make; Li, Xuefeng; Zhang, Dong; Li, Kai; Chu, Hongjun (Frontiers in Veterinary Science, 2022)
The microbiota and its metabolites play an important role in regulating the host’s metabolism and immunity. However, the mechanism behind it is still not well studied. Thus, we conducted the LC-MS/MS analysis and RNA-seq analysis on Equus przewalskii with and without horse botfly infestation to determine the metabolites produced by intestinal microbiota in feces and differentially expressed genes (DEGs) related to the immune response in blood and tried to link them together. The results showed that parasite infection could change the composition of microbial metabolites. These identified metabolites could be divided into 6 categories, including compounds with biological roles, bioactive peptides, endocrine disrupting compounds, pesticides, phytochemical compounds and lipids. The 3 pathways that most metabolites involved in were lipid metabolism, amino acid metabolism and biosynthesis of other secondary metabolites. The significant differences between host with and without parasites were shown in 31 metabolites with function known, which were related to physiological activities of host. For the gene analysis, we found that parasite infection could alarm the host’s immune response. The gene of “cathepsin W” involved in innate and adaptive immune responses was up-regulated. The two genes of the following functions were down-regulated: “protein S100-A8” and “protein S100-A9-like isoform X2” involved in chemokine and cytokine production, the toll-like receptor signaling pathway, and immune and inflammatory responses. GO and KEGG analysis showed that immune related functions of defense response and Th17 cell differentiation had significant differences between host with and without parasites respectively. At last, the relationship between metabolites and genes were determined in this study. The purine metabolism and pyrimidine metabolism contained the most altered metabolites and DEGs, which mainly influenced the conversion of ATP, ADP, AMP, GTP, GMP, GDP, UTP, UDP, UMP, dTTP, dTDP, dTMP and RNA. Thus, it could be concluded that parasitic infection can change the intestinal microbial metabolic activity and enhance immune response of host through the pathway of purine and pyrimidine metabolism. This results will be a valuable contribution to understanding the bidirectional association of parasite, intestinal microbiota and host.